Perception of Social Innovation among Management Students (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The goal of our paper is to develop and present a novel methodology of social innovation among management students. In our paper we present the understanding of the management students’ perceptions about social innovation which represents the first stage of developing and adjusting social innovation methodology to management education curriculum at a business school. Social innovation methodology is researched and implemented. We gained results in two research phases; in 2014 and 2015. Altogether, we present the results of social innovation methodology by analyzing the questionnaire results of 239 students. Social innovation achieves a systematic change for the benefit of people and planet by using specially adjusted methods for an identified social challenge. Social innovation methodology and its usage in management education setting proved to be an under-researched and highly useful didactic tool to empower students about global and local management issues.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.